Shades of Earth - Revis, Beth (Revis, Beth. Across the universe trilogy, 2013)
Leaving the walls of the spaceship Godspeed behind, Amy and Elder are ready to build a home on Centauri-Earth. But they must race to discover who--or what--else is out there if they are to have any hope of saving their struggling colony and building a future together.